Government and Community Collaboration in Kampung Tempe Economic Development Efforts Case Study: Sukomanunggal Urban Village - Anak Agung Sagung Alit Widyastuti; Bela Aldama (LPPM Universitas PGRI Adi Buana Surabaya, 2024)
Tempe Village in Sukomanunggal, Surabaya, is known for its tempe production, with most people there working as tempe makers. It's part of a government program that helps small businesses focused on tempe. This study looks at how both the community and the government contribute to local economic growth and suggests some good strategies for development. We used Participatory Foresight methods to see how the community and government work together to boost the local economy and the Analytic Hierarchy Process (AHP) to figure out the best strategies. We gathered data through observations and interviews with local business leaders, government officials, economic experts, and academics. The results show that the community helps the local economy by hiring local workers and promoting sustainable development. The government makes things easier by streamlining permits, providing equipment, and supporting branding and online marketing. This support helps tempe makers be more efficient, expand their capacity, and compete better, making Tempe Village a popular food spot. Key strategies for local economic growth include improving facilities, branding products, and offering quality training. These strategies aim to make Tempe Village’s economy stronger and more sustainable